Monetizing innovation how smart companies design the product around the price - Ramanujam, Madhavan; Tacke, Georg (Hoboken Wiley, 2016)
"Surprising rules for successful monetization Innovation is the most important driver of growth. Today, more than ever, companies need to innovate to survive. But successful innovation?measured in dollars and cents?is a very hard target to hit.  Companies obsess over being creative and innovative and spend significant time and expense in designing and building products, yet struggle to monetize them: 72% of innovations fail to meet their financial targets?or fail entirely. Many companies have come to accept that a high failure rate, and the billions of dollars lost annually, is just the cost of doing business. Monetizing Innovations argues that this is tragic, wasteful, and wrong. Radically improving the odds that your innovation will succeed is just a matter of removing the guesswork. That happens when you put customer demand and willingness to pay in the driver seat?when you design the product around the price. It?s a new paradigm, and that opens the door to true game change: You can stop hoping to monetize, and start knowing that you will. The authors at Simon Kucher know what they?re talking about. As the world?s premier pricing and monetization consulting services company, with 800 professionals in 30 cities around the globe, they have helped clients ranging from massive pharmaceuticals to fast-growing startups find success. In Monetizing Innovation, they distil the lessons of thirty years and over 10,000 projects into a practical, nine-step approach. Whether you are a CEO, executive leadership, or part of the team responsible for innovation and new product development, this book is for you, with special sections and checklist-driven summaries to make monetizing innovation part of your company?s DNA. Illustrative case studies show how some of the world?s best innovative companies like LinkedIn, Uber, Porsche, Optimizely, Draeger, Swarovski and big pharmaceutical companies have used principles outlined in this book. A direct challenge to the status quo ?spray and pray? style of innovation, Monetizing Innovation presents a practical approach that can be adopted by any organization, in any industry. Most monetizing innovation failure point home. Now more than ever, companies must rethink the practices that have lost countless billions of dollars. Monetizing Innovation presents a new way forward, and a clear promise: Go from hope to certainty"-- Provided by publisher.
"The book explains how most companies get sidetracked by Product-Driven Thinking and how to innovate by starting with the price customers will pay, and creating the product for that price. It will present a process that Simon-Kucher & Partners has used to help dozens of others avoid innovation failure by making pricing and marketing their guiding light throughout the product development process"-- Provided by publisher.
Machine generated contents note: Chapter 1: How Innovators Leave Billions on the Table: A Tale of Two Cars Chapter 2: Feature Shocks, Minivations, Hidden Gems and Undeads: The Four Flavors of Monetizing Innovation Failure Chapter 3: Why Good People Get It Wrong Chapter 4: Have the "Willingness to Pay Talk" Early: You Can't Prioritize Without It Chapter 5: Don't Default to a One-Price-Fits-All Solution: Like it or Not, Your Customers are Different Chapter 6: In Designing Products, Don't Regard Packaging and Bundling as Afterthoughts Chapter 7: Go Beyond the Flat Price: 5 Powerful Monetization Models Chapter 8: Price Low for Market Share or High for Premium Branding? Pick the Winning Pricing Strategy Chapter 9: From Hoping to Knowing: Build an Outside-In Business Case Chapter 10: The Innovation Won't Speak for Itself: You Must Communicate the Value Chapter 11: Use Behavioral Pricing Tactics to Persuade and Sell: Sometimes Your Customers Will Behave Irrationally Chapter 12: Maintain Your Price Integrity: Avoid Knee-Jerk Re-Pricing Chapter 13: Learning from the Best: Successful Innovations Designed Around the Price Chapter 14: Implementing the "Designing the Product Around the Price" Innovation Process Index.
Dr. Mary Gretchen F. Chaves (Recommending faculty) - Bookfair2017
Includes bibliographical references (pages 219-225) and index.
Keywords: New products -- Marketing; Pricing; BUSINESS & ECONOMICS / Marketing / General